HIGH SCHOOL EDUCATION REFORM: Regulatory devices and induction policies - Ribeiro Silva, Monica; Martins Oliveira, Adriana (FORMAÇÃO EM MOVIMENTO, 2024)
The text analyzes the High School reform initiated in 2016 in Brazil. Its objective is to analyze the regulations resulting from the approval of the Law and government actions for its implementation, considered, in the article, as policies that induce. This is documentary research. It discusses normative devices and induction programs based on a specialized bibliography and problematizes, especially, the implications resulting from the centrality acquired by the privatization of public education. Article published in Portuguese at Educere et Educare, [S. l.], v. 18, n. 47, p. 113–129, 2023. DOI: 10.48075/educare.v18i47.30708. Available at: https://e-revista.unioeste.br/index.php/ educereeteducare/article/view/30708.